Peran Faktor Demografi Dan Karakteristik Sosial Terhadap Kesediaan Menjalani Tes HIV Pada Perempuan Usia Reproduksi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The incidence of HIV and AIDS among women shows a significant increase, 90 % of which is infected by her sexual partner. HIV-infected status can only be detected by undergoing HIV tests; one of them is through mobile VCT services. In fact, there are women of reproductive age who are not willing to undergo HIV testing. Objective: The purpose of this study is to analyze the role of demographic factor and social characteristics towards the willingness to undergo HIV testing among women of reproductive age in the city of Bandung. Method: Research methods are case control with sampling by consecutive sampling. Research is done in 7 subdistricts in the city of Bandung during May to July 2013. The sample reaches 90 women of reproductive age following mobile VCT, 45 respondents are not willing to undergo HIV testing (case group) and 45 of whom are willing to undergo HIV testing (control group). Data collected through questionnaires are then analyzed with chi square and multiple logistic regressions. Result: The results show that demographic factors i.e. age 0,05). Social characteristics include lack of knowledge, the perception that she is not at risk, high stigma, and lack of certainty in VCT services. These influence the willingness to undergo HIV test (p